Sistem Pengelolaan Marhun Berdasarkan Perspektif PSAKS 107 pada Budaya Pata’gal lita Masyarakat Suku Mandar Sulawesi Barat - Nasmira, Nasmira; Rufaida, Erty Rospyana; Galib, Abdul (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2024)
The practice of pawning has become part of culture with the aim of helping each other. One area where this practice has become part of the culture is the Mandar tribe community in West Sulawesi. The Mandar people call it pata’gal lita. However, based on initial analysis, there are still pawning practices that are not in accordance with Islamic sharia principles. The aim of this research is to determine the management system for Marhun (Pawned Objects) based on the PSAKS 107 Perspective on the Pata’gal lita Culture of the Mandar Tribe Community of West Sulawesi. This research uses qualitative methods and is descriptive qualitative in nature. This research uses an ethnographic approach. Data was collected through interviews and documentation. Based on the research results, it is known that the system for managing pawned goods (marhun) in the Pata’gal lita culture of the Mandar Tribe Community in West Sulawesi has two forms. The first is that pawned goods (marhun) are managed in an advisory manner as long as the goods are still in pawned status. Second, pawned goods (marhun) are managed by the owner of the goods but the harvest is shared between the lender and borrower. PSAKS 107 states that murtahin should only use Marhun to cover the costs of maintenance and upkeep of pawned goods. This is considered an additional benefit of providing a loan. Because pawning is a form of mutual assistance, as is the case with debts and receivables, if there is profit obtained from debts and receivables, this is considered usury which is haram in Islamic law. [Praktik gadai telah menjadi bagian dari budaya dengan maksud untuk saling membantu. Salah satu wilayah di mana praktik ini sudah menjadi bagian dari budaya adalah masyarakat Suku Mandar di Sulawesi Barat. Masyarakat Mandar menyebutnya dengan istilah pata’gal lita. Namun, berdasarkan analisis awal, masih terdapat praktik gadai yang tidak sesuai dengan prinsip-prinsip syariah Islam. Tujuan penelitian ini adalah mengetahui sistem pengelolaan Marhun (objek gadai) berdasarkan perspektif PSAKS 107 pada Budaya Pata’gal lita Masyarakat Suku Mandar Sulawesi Barat. Penelitian ini menggunakan metode kualitatif dan bersifat deskriptif kualitatif. Penelitian ini menggunakan pendekatan etnografi. Data dikumpulkan melalui wawancara dan dokumentasi. Berdasarkan hasil penelitian diketahui sistem pengelolahan barang gadai (marhun) pada Budaya pata’gal lita Masyarakat Suku Mandar Sulawesi Barat terdapat dua bentuk. Pertama adalah barang gadai (marhun) dikelola secara menyuluh selama barang masih dalam status gadai. Kedua adalah barang gadai (marhun) dikelolah pemilik barang namun hasil panen dibagi antara pemberi pinjaman dan peminjam. PSAKS 107 disebutkan bahwa murtahin seharusnya hanya menggunakan Marhun untuk menutup biaya pemeliharaan dan perawatan barang gadai. Hal ini dianggap keuntungan tambahan dari memberikan pinjaman. Karena gadai adalah bentuk saling tolong menolong, seperti halnya dalam hutang piutang, maka jika ada keuntungan yang diperoleh dari hutang piutang, hal tersebut dianggap sebagai riba yang haram dalam hukum Islam].